SUSTAINABLE INNOVATION AND LICENSING DEVELOPMENT OF COCONUT SHELL PYROLYSIS-BASED LIQUID SMOKE HOME INDUSTRY: - - Mariany Razali; Nurmala Sari; Dewi, Dahlia Kusuma; Taufik, Muhammad (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Most residents of Manunggal Village, Labuhan Deli District, Deli Serdang Regency work in the industrial sector as employees or self-employed workers. The village has a small-scale home industry producing charcoal briquettes from coconut fiber, but it previously lacked formal licensing. The decline in briquette production alongside increasing market demand encouraged the community to shift toward liquid smoke production. This study aims to develop a legally recognized coconut-fiber–based liquid smoke home industry with enhanced production capacity. The methods included designing a pyrolysis device capable of producing liquid smoke at 650 °C for eight hours and obtaining a business license through UD Keluarga (License No. 2009240083095, 2024). The results showed increased liquid smoke output and successful legalization of the home industry, providing significant benefits to the community and supporting family economic improvement. Developing a licensed liquid smoke home industry using pyrolysis is an effective strategy to improve productivity and community welfare in Manunggal Village.